Crossing Lines — A Change in the Leading Cause of Death among U.S. Children - Lee, Lois K; Douglas, Katherine; Hemenway, David (The New England journal of medicine, 2022)
For more than 60 years, motor vehicle crashes were the leading cause of injury-related death among young people. Beginning in 2017, however, firearm-related injuries took their place to become the most common cause of death from injury.